Integrating Disability Issues into Sustainable Development Strategies - ناصر محمد عبد الرضا (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
The inclusion of persons with disabilities in sustainable development strategies is a prerequisite for achieving justice and equality, based on the Convention on the Rights of Persons with Disabilities and related legal principles, as well as the 2030 Agenda for Sustainable Development, policies and plans adopted by Member States, and institutional mechanisms that ensure the enactment and implementation of laws at the domestic level to overcome the challenges facing the inclusion process, which include discrimination, lack of funding, weak coordination, and the lack of participation of persons with disabilities in decision-making. To ensure the success of the inclusion process, this requires a radical shift from classical models to models based on rights, participation, and comprehensive design within a comprehensive development strategy for persons with disabilities, while providing mechanisms for supervision and monitoring.